Pengaruh Motivasi dan Pengalaman Kerja Terhadap Kinerja Pegawai Pada PT.YYY Manufacturing Indonesia - Alfiani Darliah, Marina Nofeline; Hartelina, Hartelina; Nurhasanah, Nunung; Jajang Suyaman , Dede (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the influence of motivation on the performance of PT TT Manucfacturing Indonesia employees. To determine the influence of work experience on the performance of employees of PT.YYY Manucfacturing Indonesia. To determine the influence of motivation and work experience together on the performance of PT.YYY. Manufacturing Indonesia. The research method used is a quantitative approach. The sample used in this research was 50 employees. The data analysis used in this research is multiple linear regression analysis with partial and simultaneous hypothesis testing. The research results show that motivation has an influence on employee performance, work experience has an influence on employee performance. There is an influence of motivation and work experience on the performance of PT employees. YYY Manufacturing Indonesia.